Ответ: x∈[-2;2).
Объяснение:
log₀,₅(12-6x)≥log₀,₅(x²-6x+8)+₀,₅(x+3)
ОДЗ:
{12-6x>0 |÷6 {2-x>0 {x<2 {x<2</p>
{x²-6x+8>0 {x²-4x-2x+8>0 {(x*(x-4)-2*(x-4)>0 {(x-4)(x-2)>0
{x+3>0 {x>-3 {x>-3 {x>-3
{x∈(-∞;2)
{x∈(-∞;2)U(4;+∞)
{x∈(-3;+∞) ⇒
x∈(-3;2).
log₀,₅(6*(2-x))-log₀,₅((x-2)(x-4))-₀,₅(x+3)≥0
![log_{0,5} \frac{6*(2-x)}{(x-2)(x-4)(x+3)} \geq 0\\\frac{6*(2-x)}{(x-2)(x-4)(x+3)} \leq 0,5^{0} \\\frac{-6*(x-2)}{(x-2)(x-4)(x+3)} \leq 1\\-6*(x-2) \leq (x-2)(x-4)(x+3)\\(x-2)(x-4)(x+3)+6*(x-2)\geq 0\\(x-2)*((x-4)(x+3)+6)\geq 0\\(x-2)(x^{2} -x-12+6)\geq 0\\(x-2)(x^{2} -x-6)\geq 0\\(x-2)(x^{2} -3x+2x-6)\geq 0\\(x-2)(x*(x-3)+2*(x-3))\geq 0\\(x-2)(x-3)(x+2)\geq 0 log_{0,5} \frac{6*(2-x)}{(x-2)(x-4)(x+3)} \geq 0\\\frac{6*(2-x)}{(x-2)(x-4)(x+3)} \leq 0,5^{0} \\\frac{-6*(x-2)}{(x-2)(x-4)(x+3)} \leq 1\\-6*(x-2) \leq (x-2)(x-4)(x+3)\\(x-2)(x-4)(x+3)+6*(x-2)\geq 0\\(x-2)*((x-4)(x+3)+6)\geq 0\\(x-2)(x^{2} -x-12+6)\geq 0\\(x-2)(x^{2} -x-6)\geq 0\\(x-2)(x^{2} -3x+2x-6)\geq 0\\(x-2)(x*(x-3)+2*(x-3))\geq 0\\(x-2)(x-3)(x+2)\geq 0](https://tex.z-dn.net/?f=log_%7B0%2C5%7D%20%5Cfrac%7B6%2A%282-x%29%7D%7B%28x-2%29%28x-4%29%28x%2B3%29%7D%20%5Cgeq%200%5C%5C%5Cfrac%7B6%2A%282-x%29%7D%7B%28x-2%29%28x-4%29%28x%2B3%29%7D%20%5Cleq%20%200%2C5%5E%7B0%7D%20%5C%5C%5Cfrac%7B-6%2A%28x-2%29%7D%7B%28x-2%29%28x-4%29%28x%2B3%29%7D%20%5Cleq%20%201%5C%5C-6%2A%28x-2%29%20%5Cleq%20%20%20%28x-2%29%28x-4%29%28x%2B3%29%5C%5C%28x-2%29%28x-4%29%28x%2B3%29%2B6%2A%28x-2%29%5Cgeq%200%5C%5C%28x-2%29%2A%28%28x-4%29%28x%2B3%29%2B6%29%5Cgeq%200%5C%5C%28x-2%29%28x%5E%7B2%7D%20-x-12%2B6%29%5Cgeq%200%5C%5C%28x-2%29%28x%5E%7B2%7D%20-x-6%29%5Cgeq%200%5C%5C%28x-2%29%28x%5E%7B2%7D%20-3x%2B2x-6%29%5Cgeq%200%5C%5C%28x-2%29%28x%2A%28x-3%29%2B2%2A%28x-3%29%29%5Cgeq%200%5C%5C%28x-2%29%28x-3%29%28x%2B2%29%5Cgeq%200)
-∞__-__-2__+__2__-__3__+__+∞ ⇒
x∈[-2;2]U[3;+∞)
Согласно ОДЗ: x∈[-2;2).